2019
DOI: 10.1080/0284186x.2018.1543948
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and toxicity of proton with photon radiation for locally advanced nasopharyngeal carcinoma

Abstract: Supplemental data for this article can be accessed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Indeed, considering our ballistic, high LET could be concentrated in the homolateral temporal lobe, and real biological dose delivered could be underestimated (11). Beddok et al reported a brain radionecrosis rate of 35% in their series of 17 patients with previously untreated stages III-IVa nasopharyngeal carcinoma (12). These patients were treated with the same protontherapy technical as in our series.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, considering our ballistic, high LET could be concentrated in the homolateral temporal lobe, and real biological dose delivered could be underestimated (11). Beddok et al reported a brain radionecrosis rate of 35% in their series of 17 patients with previously untreated stages III-IVa nasopharyngeal carcinoma (12). These patients were treated with the same protontherapy technical as in our series.…”
Section: Discussionmentioning
confidence: 69%
“…1 Radiotherapy (RT) is used in the primary treatment for NPC because of its inherent anatomic site and high radiosensitivity. 2 The currently recommended standard regimen is the addition of concurrent chemotherapy (CCRT) for NPC patients who receive RT with or without adjuvant chemotherapy being superior to radiotherapy alone. 3 Nevertheless, induction chemotherapy (IC) combined with the established CCRT regimen has attracted attention for the management of locoregionally advanced NPC (LANPC) during recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is a special cancer of head and neck, with a high incidence (15 to 50 cases per 100,000 persons annually) and main causes of cancer death (50,000 persons per year) in endemic regions such as Southern China, Southern Asia, the Middle East, Northern Africa, Singapore, and Malaysia [1]. Radiotherapy (RT) is used in the primary treatment for NPC because of its inherent anatomic site and high radiosensitivity [2]. The currently recommended standard regimen is the addition of concurrent chemotherapy (CCRT) for NPC patients who receive RT with or without adjuvant chemotherapy being superior to radiotherapy alone [3].…”
Section: Introductionmentioning
confidence: 99%